The Economic Determinant Factors of Indonesia Crude Palm Oil Exports to India - Teguh Warsito (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2020)
This study examines the economic determinants of Indonesia Crude Palm Oil (CPO) export performance to India using time series data from quarter 1, 2006 to quarter 2, 2016. India is one of Indonesia's main export destinations for CPO commodities. The results indicate that the price of soybean oil, as a substitution good of CPO, significantly influences the value of CPO exports. Another variable that significantly affects the CPO exports is the Gross Domestic Product of India as a proxy for the demand of CPO. Although the exchange rate and total production of CPO positively influence the CPO exports, the effects of these variables are too weak, not significant. As the largest exporter of CPO in the world, the Indonesia government should maintain the fluctuation of CPO price, relative to the price of soybean as substitution goods, in the international market. Furthermore, monitoring the global economies, such as the fluctuation of GDP India as the market, is very important to capture the opportunity to increase CPO exports.